PEMANFAATAN KEARIFAN LOKAL DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR : SYSTEMATIC LITERATURE REVIEW - Nurjanah, Ika; Puspitasari, Wina Dwi; Febriyanto, Budi; Rosidah, Ani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social Studies (IPS) learning in elementary schools plays a crucial role in shaping students' social understanding, cultural awareness, and character from an early age. One relevant approach to enhancing the meaningfulness of IPS learning is the utilization of local wisdom as a contextual learning resource that is close to students' lives. This study aims to systematically examine the utilization of local wisdom in IPS learning in elementary schools and its contribution to the development of students' cognitive, affective, social, and skills. This study employs a descriptive qualitative approach, utilizing the Systematic Literature Review (SLR) method to analyze relevant research articles. Data analysis was conducted narratively and thematically to identify the forms of local wisdom utilized, how they are integrated into IPS learning, the learning approaches used, and the resulting impacts. The results of the study indicate that the utilization of local wisdom in IPS learning consistently has a positive impact on students' understanding of IPS concepts, character building, cultural awareness, social skills, and thinking abilities. However, most research remains contextual and limited to specific regions, so further studies are needed with a more comprehensive scope and methodological approach.